Modern Opportunities for Improvement Development of the Logistics Level in Meat Processing Organizations in Bulgaria - Vodenicharova, Maria (Research Papers, 2014)
The thesis of present research is development of logistics in the meat processing organizations in Bulgaria does not respond contemporary requirements, hence there is a need of active and urgent changes. It has to be elaborated a clear vision for improvement logistics development with compliance both: with the Bulgarian conditions in meat processing organizations and the foreign practice in the more advanced countries.The goal of research is to evaluation of the degree of development of logistics in the meat processing organizations in Bulgaria from the point of view of the logistics development. The object of the industry is the meat processing companies in Bulgaria.In order to study the state and development of the meat industry logistics in Bulgarian meat processing organizations, a wide range of statistical and analytical methods are used (comparison, group average, graphical method, cluster analysis and others). The date processing in done by a computer program for statistical date processing –SPSS (Statistical Package for Social Sciences).In terms of level of development of logistics, the surveyed organizations are separated into three clusters: cluster 1 - organizations which do not apply logistics concept, the second cluster includes organizations which have a growing interest in logistics concept, and the third cluster which includes meat processing organizations, where the role of logistics is important and apply the logistic concept to a large extent.The vision of improvement of the logistics is appointed, having regard to both the Bulgarian conditions in the meat processing organizations and foreign practice in advanced countries. From this perspective, the indicators of the level of development of logistics model follow a smooth transition from in-company integration to inter-company integration. The present work represents consecutively the stages of changes in meat processing organizations, which replies of the tree stages of the logistics development.